2021
DOI: 10.3390/batteries7040067
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature and Electrolyte Composition on the Performance of Lithium Metal Anodes

Abstract: Lithium metal anodes have again attracted widespread attention due to the continuously growing demand of cells with higher energy density. However, the lithium deposition mechanism and the affecting process of influencing factors, such as temperature, cycling current density, and electrolyte composition are not fully understood and require further investigation. In this article, the behavior of lithium metal anode at different temperatures (25, 40, and 60 ∘C), lithium salts, electrolyte concentrations (1 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Besides, due to the reaction between the Li plating and the electrolyte, the gas is generated earlier and the internal pressure is too high. Boroujeni's team [94] investigated the battery behavior of anodes with different Li salts (LiFSI and LiTFSI), electrolyte concentrations (1 and 2 M), and rates (equivalent to 0.5 C, 1 C, and 2 C) at different temperatures (25, 40 and 60 °C). Through the analysis, it is found that the long cycle life and relatively good CE are obtained by 2 C fast‐charging of batteries with high concentration of LiFSI in 1,2‐DME electrolyte at 25 °C.…”
Section: Thermal Issues Related With Fast‐chargingmentioning
confidence: 99%
“…Besides, due to the reaction between the Li plating and the electrolyte, the gas is generated earlier and the internal pressure is too high. Boroujeni's team [94] investigated the battery behavior of anodes with different Li salts (LiFSI and LiTFSI), electrolyte concentrations (1 and 2 M), and rates (equivalent to 0.5 C, 1 C, and 2 C) at different temperatures (25, 40 and 60 °C). Through the analysis, it is found that the long cycle life and relatively good CE are obtained by 2 C fast‐charging of batteries with high concentration of LiFSI in 1,2‐DME electrolyte at 25 °C.…”
Section: Thermal Issues Related With Fast‐chargingmentioning
confidence: 99%
“…Under this background, the development of renewable clean energy, including wind, solar and electrochemical storage technology, is of great significance to the sustainable application of energy. Among them are rechargeable lithium metal batteries (LMBs); their high-energy-density has drawn much attention around the world [ 1 , 2 , 3 , 4 , 5 ]. In recent years, LMBs have been regarded as the ideal choice to replace traditional lithium-ion batteries in the stationary energy storage field and electric vehicles [ 6 , 7 , 8 , 9 , 10 ]; however, accompanied by the application of highly active metallic Li anodes, safety concerns for LMBs also increased.…”
Section: Introductionmentioning
confidence: 99%